THE BLOCKCHAIN TECHNOLOGY SOLUTION TO THE PAIN POINTS OF LETTER OF CREDIT (Third Sector Social Economic Review, 2025)
Blockchain, decentralized and distributed ledger elements and smart contract, data security, transparency, speed, etc. advantages are revolutionary and will have a significant impact on improving and reshaping trade.The purpose of this study is to investigate the elimination of disadvantages such as problematic points, transaction risks and costs of Letter of Credit, which is accepted as the most secure payment method in international trade, and in addition to this, general risk elements for the value flow of cross-border trade, with the gains of blockchain technology.The study reveals the elements of the blockchain and the concepts developed with this technology. In the research, where the current structure, risk elements and inefficient aspects of the letter of credit process were determined, a process prototype developed with blockchain integration was created to improve the critical points of the process. The elements of supply chain, international financial transactions, and letter of credit payment method processes such as contract, letter of credit opening, documentation, shipment, transfer handled with blockchain technology, were compared between the traditional structure and the desired structure and interpreted with the inferences obtained from the studies in the literature. The workflow automation design in the letter of credit payment system and supply chain process, which is achieved by integrating the distributed ledger technology of the blockchain and the smart contracts created depending on it, concretizes the study. With this feature, the study provides guidance to those who develop models for this process or similar commercial processes and contributes to the literature.
Keywords: Blokchain; Smart Contracts; Letter of Credit; International Trade; Supply Chain